Somatically mutated ABL1 is an actionable and essential NSCLC survival gene. Issue 2 (12th January 2016) - Testoni, Ewelina; Stephenson, Natalie L; Torres‐Ayuso, Pedro; Marusiak, Anna A; Trotter, Eleanor W; Hudson, Andrew; Hodgkinson, Cassandra L; Morrow, Christopher J; Dive, Caroline; Brognard, John
Abstract: The lack of actionable mutations in patients with non‐small cell lung cancer (NSCLC) presents a significant hurdle in the design of targeted therapies for this disease. Here, we identify somatically mutated ABL1 as a genetic dependency that is required to maintain NSCLC cell survival. We demonstrate that NSCLC cells with ABL1 mutations are sensitive to ABL inhibitors and we verify that the drug‐induced effects on cell viability are specific to pharmacological inhibition of the ABL1 kinase. Furthermore, we confirm that imatinib suppresses lung tumor growth in vivo, specifically in lung cancer cells harboring a gain‐of‐function (GOF) mutation in ABL1. Consistent with structural modeling, we demonstrate that mutations in ABL1 identified in primary NSCLC tumors and a lung cancer cell line increase downstream pathway activation compared to wild‐type ABL1. Finally, we observe that the ABL1 cancer mutants display an increased cytosolic localization, which is associated with the oncogenic properties of the ABL1 kinase. In summary, our results suggest that NSCLC patients with ABL1 mutations could be stratified for treatment with imatinib in combination with other therapies. Synopsis: Somatically mutated ABL1 is defined as a novel druggable driver in lung adenocarcinoma where mutant forms of ABL1 kinase promote increased survival and proliferation, altered localization, and enhanced downstream pathway activation. Lung cancer cells harboring ABL1 mutations are sensitive to ABL inhibitors. Depletion of mutant ABL1 suppresses lung cancer cell viability. ABL1 mutations alter localization and increase downstream pathway activation. ABL1 mutants promote cell survival and proliferation. Abstract : Somatically mutated ABL1 is defined as a novel druggable driver in lung adenocarcinoma where mutant forms of ABL1 kinase promote increased survival and proliferation, altered localization, and enhanced downstream pathway activation.